(untitled) (Forum Penelitian Agro Ekonomi, 2016)
Agricultural sector has a very strategic role in the national development. Nevertheless, the agricultural sector still deals with some problems, e.g. lack of capital for farmers and agricultural business. National banks, theoretically, have a significant potential for agricultural financing because of their core business as the financial intermediary institution. However, the facts show that national banking credit to the agricultural sector is still limited, that is less than 6 percent. This paper aims to review potential, role and the constraint of national banks in financing the agricultural sector. The study shows that the lack of financing in the agricultural sector by national banks caused by high risk in the agricultural sector, complicated term in credit proposal, poor management of agricultural businesses due to its micro-small scale, and limited competence of bank in the field of agricultural finance. The government tries to increase agricultural finance through increasing budget allocation to this sector, improving effectiveness of state budget funds, or formulating an alternative financing scheme in accordance with the characteristics of agriculture.